Perioperative Management of Extended-release Buprenorphine. Issue 1 (22nd January 2023) - Hickey, Thomas R.; Henry, Jonathan T.; Edens, Ellen L.; Gordon, Adam J.; Acampora, Gregory
Abstract : Perioperative management of buprenorphine is increasingly characterized by continuation of buprenorphine throughout the perioperative period while coadministering full agonist opioids for analgesia. Although this "simultaneous strategy" is commonly used for the shorter-acting sublingual buprenorphine formulations, there is little to guide management of the extended-release formulations of buprenorphine. Here we report the perioperative experience of an individual maintained on extended-release buprenorphine who successfully underwent major surgeries utilizing a strategy of performing the surgeries at the time of the next scheduled dose.